2009
DOI: 10.1002/job.633
|View full text |Cite
|
Sign up to set email alerts
|

Work characteristics, challenge appraisal, creativity, and proactive behavior: A multi‐level study

Abstract: SummaryWork characteristics such as time pressure and job control can be experienced as a challenge that is positively associated with performance-related behaviors. Using experience-sampling data from 149 employees, we examined the relationships between these work characteristics and creativity and proactive behavior on a daily level. Results from multilevel analyses indicate that time pressure and job control are perceived as challenging, and that challenge appraisal in turn is related to daily creativity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
397
4
13

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 441 publications
(434 citation statements)
references
References 85 publications
20
397
4
13
Order By: Relevance
“…To date, empirical research has yielded mixed and inconsistent results as to whether time pressure undermines or enhances creativity (Anderson, Potočnik & Zhou 2014;Amabile et al 2002;Andrews & Farris 1972;Baer & Oldham 2006;Ohly & Fritz 2010). We found three empirical studies that demonstrated a negative effect of time pressure on creativity.…”
Section: Perceived Time Pressure and Creativitymentioning
confidence: 73%
See 2 more Smart Citations
“…To date, empirical research has yielded mixed and inconsistent results as to whether time pressure undermines or enhances creativity (Anderson, Potočnik & Zhou 2014;Amabile et al 2002;Andrews & Farris 1972;Baer & Oldham 2006;Ohly & Fritz 2010). We found three empirical studies that demonstrated a negative effect of time pressure on creativity.…”
Section: Perceived Time Pressure and Creativitymentioning
confidence: 73%
“…Therefore, we hypothesized an inverted Ushaped relation between overall perceived time pressure and creativity. Surprisingly, results showed a U-shaped relationship, suggesting that a) high levels of time pressure will result in more creativity since high time pressure may be perceived as challenging, and challenge appraisal in turn is related to creativity (Ohly & Fritz 2010) and b) low levels of time pressure will also facilitate creativity by allowing employees to have enough time to engage in multiple roles (Coverman 1989), which enables interaction with different people and support from colleagues and family when necessary. This finding presents the study's first theoretical contribution to the creativity literature by providing evidence of the existence of a curvilinear, Ushaped relation between perceived time pressure and creativity.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, those lower in proactive personality are less likely to enhance their sense of competence from engaging in proactive behavior, not only because they tend not to do so, but also because they may not appreciate such experiences as being dominant and taking risks to challenge status quo can make them full uncomfortable (Côté & Moskowitz, 1998). Although those lower in proactive personality may behave proactively when they need to (Ohly & Fritz, 2010;Wu, Parker, & de Jong, 2014), they are less likely to attribute a competent view to themselves from engaging in such behavior because their proactive behavior is triggered by external demands. Moreover, they will not be granted a "proactive" badge from others if they are forced to engage in proactive behavior.…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…As the differentiation between job demands and challenges was more apparent at the daily level, it is possible that characteristics such as problem solving are perceived as a challenge in the short term, but as a demand or a cost in the long term. Although there is no empirical evidence, to the author's knowledge, which demonstrates differences in the appraisal of chronic and temporal demands, there is evidence to suggest that coping and regulation processes are apparent at a daily level (Ohly & Fritz, 2010;Schmitt, Zacher & Frese, 2012). Ohly and Fritz (2010) for example, suggest that individuals who desire changes in their work conditions might appraise their situation as challenging at that time.…”
Section: Question 1: How Are Jobs Designed Under Lean Manufacturing?mentioning
confidence: 99%